1999
DOI: 10.1101/gad.13.5.532
|View full text |Cite
|
Sign up to set email alerts
|

The conserved protein kinase Ipl1 regulates microtubule binding to kinetochores in budding yeast

Abstract: Chromosome segregation depends on kinetochores, the structures that mediate chromosome attachment to the mitotic spindle. We isolated mutants in IPL1, which encodes a protein kinase, in a screen for budding yeast mutants that have defects in sister chromatid separation and segregation. Cytological tests show that ipl1 mutants can separate sister chromatids but are defective in chromosome segregation. Kinetochores assembled in extracts from ipl1 mutants show altered binding to microtubules. Ipl1p phosphorylates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
394
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(415 citation statements)
references
References 56 publications
21
394
0
Order By: Relevance
“…We introduced a GAL1-IPL1 allele into a strain with LacO sequences at TRP1 and LYS4. Overexpression of IPL1 has no obvious detrimental effect on cell growth (Biggins et al, 1999; data not shown), but we observed that ϳ50% of cells with large buds contained a condensed chromosome IV compared with ϳ20% in control cells not overexpressing IPL1. We therefore released cells from a G1 synchrony and asked if overproduction of the Ipl1 kinase could promote maintenance of chromosome IV condensation in the presence of nocodazole.…”
Section: Condensation Of Chromosome IV Can Be Restored By Overexpressmentioning
confidence: 81%
“…We introduced a GAL1-IPL1 allele into a strain with LacO sequences at TRP1 and LYS4. Overexpression of IPL1 has no obvious detrimental effect on cell growth (Biggins et al, 1999; data not shown), but we observed that ϳ50% of cells with large buds contained a condensed chromosome IV compared with ϳ20% in control cells not overexpressing IPL1. We therefore released cells from a G1 synchrony and asked if overproduction of the Ipl1 kinase could promote maintenance of chromosome IV condensation in the presence of nocodazole.…”
Section: Condensation Of Chromosome IV Can Be Restored By Overexpressmentioning
confidence: 81%
“…The IPL1 gene was identi®ed originally in a screen for yeast mutants that increase in ploidy (Francisco et al, 1994). The yeast IPL1 may regulate kinetochore function via phosphorylation of Ndc10p (Biggins et al, 1999). Embryos derived from aurora mutant mothers display closely paired centrosomes and monopolar spindles (Glover et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies indicated that ipl1 and sli15 mutant cells showed frequent chromosome missegregation (Chan & Botstein 1993;Kim et al 1999). Subsequently, we and other groups discovered that sister centromeres were frequently pulled to one pole (w70%) when a bipolar spindle was established in these mutant cells (Biggins et al 1999;He et al 2001;Tanaka et al 2002).…”
Section: Roles Of the Ipl1-sli15 (Aurora B-incenp) Kinase Complex In mentioning
confidence: 99%